FAKTOR RISIKO KEJADIAN STUNTING PADA BALITA USIA 24-36 BULAN DI PUSKESMAS DELI TUA KECAMATAN DELI TUA KABUPATEN DELI SERDANG - Tetty Junita Purba (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2023)
Stunting is a linear growth disorder characterized by a high z-score for age <10 years. It showed -2 ​​SD. Deritua's prevalence health center is 2.71% of him. This study addressed risk factors for stunting in infants aged 24 to 36 months in relation to family economic factors, nutritional status, exclusive breastfeeding, immunization status, and infectious disease status. increase. The aim of this study was to analyze risk factors for developmental delay in infants aged 24-36 months. This research method was descriptive in cross-sectional design. Sampling is done by simple random sampling with a sample size of 40 people. Stunting is measured based on age-specific z-scores and nutritional status as weight divided by height. Analysis using Sofwere World Health Organization (WHO) Anthro 2005. Data on economic status, immunization status, and infectious disease status were measured using questionnaires and maternal and child health handbooks. Infant height was measured with a microtooth and infant weight was measured with a scale. Data analysis with chi-square. The outcome of this study was a prevalence of growth retardation of up to 32.5%. The bivariate outcome was that risk factors for stunting in infants aged 24–36 months were family economic status < UMR p=0.00 (p<0.05), normal nutritional status p=0.00 (p<0.05). 0.05), indicating exclusive breastfeeding. Breast milk alone p=0.00 (p<0.05), full vaccination status p=0.05 (p<0.05). Infections have not been proven to be a risk factor for growth retardation in infants. The results of this study are that economic status, nutritional status, exclusive breastfeeding, and immunization status are risk factors for growth retardation in infants aged 24-36 months.